1995
DOI: 10.2330/joralbiosci1965.37.356
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on cell interaction between fibroblasts of periodontal ligament and cells from Malassez epithelial rests co-cultured in vitro.

Abstract: : The purpose of this studywas to investigate the interaction between cells from Malassez epithelial rest (MER) and fibroblasts of periodontal ligament (PLF) co-cultured in vitro. MER formed typical pavement-like sheets, whilePLF were characterized by a long, slender shape and were arranged in a characteristic storiform pattern. PLF showed a marked increase in the number of cells on a daily basis, and cell proliferation followed an arithmetical progression. In contrast, MER exhibited a much lower proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Moreover, the possibility that some materials secreted by the Malassez epithelial rest suppress the proliferation of fibroblasts can be envisaged. The process may correlate closely with the homeostasis function and prevention of ankylosis (Inoue et al, 1995b).…”
Section: Homeostasis Functions Periodontal Ligament In Transplantationmentioning
confidence: 99%
“…Moreover, the possibility that some materials secreted by the Malassez epithelial rest suppress the proliferation of fibroblasts can be envisaged. The process may correlate closely with the homeostasis function and prevention of ankylosis (Inoue et al, 1995b).…”
Section: Homeostasis Functions Periodontal Ligament In Transplantationmentioning
confidence: 99%
“…Inoue et al reported interactions between ERM cells and PDL fibroblasts using co-cultures in vitro, but they cultured ERM cells and PDL fibroblasts that were mixed in the bottom of each culture dish (14). In contrast, our study used a co-culture system in which a membrane with 0.4 μm pores allowed the exchange of medium, including factors secreted by ERM cells, but cell-to-cell interactions between ERM cells and PDL fibroblasts were inhibited (16).…”
Section: Discussionmentioning
confidence: 73%
“…Periodontal tissues were obtained from the premolars of swine, according to the method of Inoue et al (14). PDL fibroblasts were then incubated in a humidified atmosphere of 95% air and 5% CO2 at 37℃ for primary culture, using alpha-minimal essential medium (Gibco, Invitrogen Corporation, Carlsbad, CA, USA) containing 10% fetal bovine serum (Sigma, St Louis, MO, USA) supplemented with 2 ml gentamycin (10 mg/ml, Sigma).…”
Section: Pdl Fibroblasts and Erm Cellsmentioning
confidence: 99%